2017
DOI: 10.1503/cjs.004317
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic use among older adults on an acute care general surgery service

Abstract: Background: Antibiotics play an important role in the treatment of many surgical diseases that affect older adults, and the potential for inappropriate use of these drugs is high. Our objective was to describe antibiotic use among older adults admitted to an acute care surgery service at a tertiary care teaching hospital.Methods: Detailed data regarding diagnosis, comorbidities, surgery and antibiotic use were retrospectively collected for patients 70 years and older admitted to an acute care surgery service. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 51 publications
(49 reference statements)
0
2
0
Order By: Relevance
“…We are aware of the high and often inappropriate prescribing and dispensing of antibiotics in ambulatory care [1,[21][22][23][24][25]] driving up AMR rates. However, there is also high and inappropriate use of antibiotics in hospitals in both high income [26][27][28][29][30][31][32][33] as well as in low and middle income countries (LMICs), driven in some countries by high rates of sexually transmitted infections, HIV, TB and malaria among in-patients [34][35][36][37][38][39][40][41]. A key step to improving antimicrobial use in hospitals is to monitor current utilization patterns and instigate activities to improve this where pertinent via Drugs and Therapeutics Committees (DTCs) and antimicrobial stewardship programmes (ASPs) [11,35,39,[42][43][44][45][46].…”
Section: Introductionmentioning
confidence: 99%
“…We are aware of the high and often inappropriate prescribing and dispensing of antibiotics in ambulatory care [1,[21][22][23][24][25]] driving up AMR rates. However, there is also high and inappropriate use of antibiotics in hospitals in both high income [26][27][28][29][30][31][32][33] as well as in low and middle income countries (LMICs), driven in some countries by high rates of sexually transmitted infections, HIV, TB and malaria among in-patients [34][35][36][37][38][39][40][41]. A key step to improving antimicrobial use in hospitals is to monitor current utilization patterns and instigate activities to improve this where pertinent via Drugs and Therapeutics Committees (DTCs) and antimicrobial stewardship programmes (ASPs) [11,35,39,[42][43][44][45][46].…”
Section: Introductionmentioning
confidence: 99%
“…Ceftriaxone was the most usually administered third generation cephalosporin in most surgeries; however, cefotaxime or cefoperazone was apparently the most regularly prescribed third generation cephalosporin in a few studies [17,[27][28][29][30]. It has been reported that the most common therapeutic errors in general surgery were administration of second-or third-line antibiotics without indication and use of antibiotics when they were not required [31,32]. Therefore, it is plausible that geographical differences in bacterial susceptibility and resistance, and infectious disease prevalence in different regions and nations could affect the prescribing behaviors [6,7,28].…”
Section: Discussionmentioning
confidence: 99%